VACCINATION OF JUVENILE TIGER GROUPER WITH THREE INACTIVATED BACTERIAL PATHOGENS - . Zafran (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
An experiment to evaluate the efficacy of inactivated polyvalent bacterial vaccines to increase specific immunity of tiger grouper (Epinephelus fuscoguttatus) against bacterial infection was conducted in floating net cages located in Sumbawa Island, West Nusa Tenggara. Polyvalent bacterial vaccine was prepared by mixing three species of killed-bacteria (Vibrio harveyi, V. alginolyticus, and Photobacterium leiognathi) with ratio of 1:1:1. The density of bacterial vaccine was adjusted at 1010 CFU/ml. The vaccines were delivered by immersion. The control fish were immersed in sea water without vaccine. Fish with ± 6 cm of total length and ± 7 g of body weigth were used in this experiment. The fishes were reared in concrete tanks in hatchery of Gondol, Bali until they reached ± 9 cm of total length. Later, the fishes were reared for 6 months in floating net cages located in Sumbawa. Re-vaccinations were delivered 60 days and 120 days post initial vaccination. The results showed that titer antibody and survival rate of the vaccinated fish were 1/128 and 77.11%, higher than the control (titer antibody=1/4-1/8, survival=45.56%, respectively). The relative percent survival of the vaccinated fish was 57.95%. It was suggested that the vaccines were immunogenic and had protective ability against bacterial infection in tiger groupers. Keywords: bacterial disease, polyvalent bacterial vaccine, tiger grouper